Convergent and known group validity of the STarT Back Tool in a Nigerian population with chronic low back pain - Mbada, Chidozie Emmanuel; Ojo, Joshua Oluwafunmibi; Idowu, Opeyemi Ayodiipo; Afolabi, Taofik Oluwasegun; Afolabi, Aanuoluwapo Deborah; Oke, Kayode Israel; Sonuga, Oluwatobi Ademola; Karstens, Sven; Fatoye, Francis (physioscience, 2021)
Background The STarT Back Tool (SBT) was developed to aid the stratification of patients with low-back pain (LBP), based on future risks for physical disability.Objective Investigation of the convergent and known group validity of the SBT in a Nigerian population with chronic LBP using disability-related psychosocial outcomes.Method Cross-sectional study involved 30 consenting patients with chronic LBP in an outpatient physiotherapy clinic of a tertiary health institution in Nigeria. Future risk of disability was assessed using the SBT. Psychosocial variables of pain catastrophizing, fear-avoidance beliefs (FAB), and kinesiophobia were assessed using the Pain Catastrophizing Scale, the Fear-Avoidance Beliefs Questionnaire and the Tampa Scale of Kinesiophobia, respectively. Data was analysed using percentages and Spearman correlation.Results Based on the SBT, there were rates of 43.3 % and 23.3 % for low and high future risks of physical disability. The median score of pain catastrophizing was 13.5, that of FAB came in at 16.5 related to physical activity and 14.0 related to work, and the score for kinesiophobia amounted to 39. The SBT total scores moderately correlated with the FAB related to work (rho = 0.45 (95 % CI 0.09–0.700). FAB related to physical activity (p = 0.040) significantly differed across the SBT subgroups.Conclusion The SBT and the other psychosocial instruments used in this study did not correlate to a sufficient degree. In addition, patients exhibiting catastrophizing, fear-avoidance beliefs, or kinesiophobia could not be differentiated based on SBT risk groups. The results should be interpreted with caution until findings from additional studies with sufficient sample sizes are at hand.
Keywords: low-back pain; disability; risk; STarT Back Tool; Nigeria